Strategic Communication Leadership in International Security Crises: A Case Study of Military Discourse in the Russo‑Ukrainian Conflict - Zamfirescu, Cornel (Acta Universitatis Danubius. Relationes Internationales, 2025)
This study critically examines how senior Ukrainian military leaders exercised communication leadership during the 2022–2023 hybrid crisis, situating strategic messaging within the broader framework of defense diplomacy and international legitimacy. Drawing on theoretical frameworks in strategic narrative (Navumau et al., 2024) and crisis communication within hybrid warfare contexts, the analysis builds upon situational crisis communication theory to contextualize how discourse can mitigate reputational threats. Through qualitative thematic content analysis, the article systematically evaluates official speeches, press releases, social media messaging, and rapid-response platforms, highlighting shifts in discourse in response to Russian disinformation campaigns. The findings reveal a deliberate transition toward proactive, narratively coherent, and digitally adaptive communication, emphasizing transparent yet strategically calibrated messaging. This approach corresponded with substantial increases in public trust, rising above 80% and reinforced Ukraine’s credibility within NATO-aligned international networks. The study underscores the pivotal role of communicational leadership in sustaining military legitimacy and alliance cohesion, advocating for its integration into defense governance, crisis protocols, and IR scholarship on information resilience. By offering original empirical insights into the communicational dimension of hybrid warfare, this article equips military educators, policymakers, and international relations scholars with a refined framework for understanding and operationalizing discourse as strategic defense in contested security environments.